Long-slit spectral study of the unusual post-interacting galaxy Arp 263 - Zasov, Anatoly V.; Saburova, Anna S; Egorov, Oleg; Lander, Vsevolod Yu; Afanasiev, Victor L; Uklein, Roman I (Monthly notices of the Royal Astronomical Society, 2024)
Arp 263 is a single irregularly shaped galaxy with intense star formation. Its short tidal features of low brightness visible in both optics and the H i line, as well as the strong non-circular motion of atomic gas in the outskirts, give pieces of evidence of a recent merging with some intruder, non-observed directly. We carried out spectral observations of this galaxy at the 6 m telescope of the Special Astrophysical Observatory. The spectra for three positions of the spectral slit were obtained: two of them cross the central region of the galaxy and the third one runs along the nearly straight narrow chain of clumps of emission gas with a length of 4-5 kpc. We derived the profiles of velocity, fluxes, and oxygen abundances (O/H) along the slits. We confirm that within the radius of several kpc the galaxy rotates regularly. The maximal value of the rotational velocity allows us to conclude that the dark mass of the galaxy prevails over the mass of its visible components. The observed velocity profile along the peripheral star-forming chain gives pieces of evidence that it is located outside of the plane of the disc, and the gas that formed the chain is probably falling back on to the disc after being ejected from the galaxy. We discuss that the observed chain of clumps is the result of gravitational instability of the gaseous filament.
Online verfügbar: 2023 December 23
Gesehen am 17.06.2024